Is There Always a Trade-off between Insurance and Incentives? The Case of Unemployment with Subsistence Constraints - Juliana Mesén Vargas; Bruno Van der Linden (Institute of Labor Economics (IZA), 2017)
This article analyzes the behavioral effects of unemployment benefits (UB) and it characterizes their optimal level when jobless people only survive if they have access to a minimum or subsistence consumption level in each period. To survive when the level of UB is very low, they carry out a subsistence activity. Our model shows that if the level of UB is very low, increasing its level or providing liquidity to the agent can decrease the duration in unemployment; for higher levels of UB we reencounter the standard properties that increasing UB increases duration and that providing liquidity to the agent increases duration (Chetty, 2008). We also show that the optimal level of UB satisfies the Baily-Chetty formula (Baily, 1978, Chetty, 2006), but contrary to Chetty (2008), in our model the gain from insurance cannot be rewritten using sufficient statistics; we show that such decomposition requires specific modeling assumptions.
Keywords: D91; H21; J64; J65; 330; liquidity effect; scarcity; monetary costs; optimal insurance